Impact of Classic Music Intervention on Anxiety Levels of Medical Students during Online Learning on COVID-19 Pandemic - Vanessa, Irene; Suryani, Eva; Steffanus, Mario (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: Situation of COVID-19 pandemic has become a global health problem and has caused public health anxiety, especially for medical students. Anxiety disorder experienced by a person can be treated by pharmacological or non-pharmacological therapy. One of many procedures of non-pharmacological treatments that can be done is by intervening in western classical instrumental music. According to existing studies, music interventions are known to have the effect of providing calm, elevating mood, and making a person feel more relaxed. This study aimed to determine the effectiveness of receptive western classical instrumental music intervention in overcoming anxiety disorders in preclinical medical students of FKIK Atma Jaya University during online classroom learning during the COVID-19 pandemic.Methods: This study was an experimental study composed of a single group with a research design of pre-test and post-test done by 78 medical students from FKIK UnikaAtma Jaya Batch 2021. The measuring instrument used was the GAD-7 questionnaire. The data analysis performed was univariate, bivariate, and multivariate analysis.Results: There were 78 respondents, with the majority aged 17-18 years old. The majority gender was female (61.54%). Most of the respondents were in the upper socioeconomic class (84.62%). The 78.21% of students live with their parents. Bivariate analysis showed a decrease in student anxiety before and after the music intervention. Multivariate analysis showed a significant relationship between anxiety level and place of residence.Conclusion: Western instrumental classical music can reduce anxiety in medical students of FKIK UnikaAtma Jaya Batch of 2021 during online learning.